ANALYSIS COMPOSITION WEIGHT AND TYPE OF CATCHES OF BEACH SEINE WHICH OPERATED AT MORNING AND AFTERNOON IN BUNGUS SELATAN VILLAGE BUNGUS TELUK KABUNG DISTRICT PADANG CITY PROVINCE OF WEST SUMATERA - Suherman '; Arthur Brown; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on 14 - 21 April 2015 in Bungus Selatan village Bungus Teluk Kabung district Padang city Province of West Sumatera. The purpose of this research was conducted to determine differences in the weight composition and species catch of beach seine operated in the morning and afternoon and looking appropriate operating time to perform better operation beach seine. The method used in this research is the survey method. Catches obtained during the afternoon compared to the catch in the morning, there is no difference in species and weight composition of beach seine catches in the morning and afternoon.Keywords: Difference, Catch composition, beach seines, Comparison Catch